The Relation Between The Intensity of Market Competition, Intellectual Capital, Management Accounting Practices in Coventional and Digital SME - Rachmawati, Dyna; Kristina, Natalia; Chow Poh Ling (Universitas Muhammadiyah Surakarta, 2023)
This study investigates the difference of the impact of external and internal environment on the use of management accounting practices between conventional and digital SMEs. The use of management accounting practices assists the SMEs to make good decision. The aim of the study to test the relationship between intensity of market competition (external environment) and intellectual capital (internal environment) on the use of management accounting practices, so that the SMEs leverage their performance. The population of this research is conventional and digital SMEs in East Java. This study uses the convenience method as a sampling technique. The data collection results are 179 SMEs consisting of 127 conventional and 52 digital SMEs. The test results with SMART-PLS show that (1) the intensity of market competition has a positive effect on intellectual capital both conventional and digital SMEs, (2) intellectual capital has a positive effect on traditional MAP and on contemporary MAP both conventional and digital SMEs, (4) traditional MAP has a positive effect on business performance in conventional SMEs, and (5) contemporary MAP has no effect on business performance in digital SMEs.